Edukasi Penanganan Risiko Jatuh untuk Mencegah Cedera Spinal pada Pasien Pascaoperasi dengan Regional Anestesi - M. Irhamnur Bagusya; Made Suandika; Adiratna Sekar Siwi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Patients undergoing regional anesthesia are at increased risk of falls during the early postoperative period due to temporary motor and sensory impairment, as well as orthostatic hypotension. Falls may result in serious complications, including spinal cord injury. Therefore, health education on fall risk prevention and safe mobilization is essential to improve patient safety during recovery. Objective: To improve patients' knowledge regarding fall prevention through health education and safe mobilization demonstrations among postoperative patients receiving regional anesthesia. Method: This community service program was conducted in the Recovery Room of RSI Purwokerto involving 30 postoperative patients receiving regional anesthesia. Activities included fall risk screening using the Morse Fall Scale, motor function assessment using the Bromage Score, sensory block assessment, pre-test, health education using leaflets, safe mobilization demonstrations, discussion, and post-test evaluation. The results were analyzed descriptively using frequency and percentage distributions. Result: Most participants were classified as having a moderate fall risk (53.3%). Before mobilization, all participants had a Bromage Score of 3 (100%). After safe mobilization, 66.7% improved to Bromage Score 2. Participants with good knowledge increased from 83.3% before education to 100% after the intervention. Conclusion: Health education combined with fall risk screening, motor function assessment, and safe mobilization demonstrations improved patients' knowledge and supported safer postoperative mobilization. This program can be implemented as part of patient safety improvement efforts in the recovery room.